Petrography, geochemistry, and zircon U–Pb chronology of the Late Ordovician metavolcanic suites in the eastern North Qilian orogenic belt, NW China: constraints on their petrogenesis and tectonic implications - Hussain, Irshad; Li, Zuochen; Pei, Xianzhi; Pei, Lei; Gao, Feng; Wang, Mao; Wang, Xiao; Lin, Hao; Qin, Li; Ji, Shang (Acta geochimica, 2025)
The study area is situated in the Tianshan region, specifically within the eastern segment of the North Qilian Orogenic Belt (NQLOB). The NQLOB is a critical region for understanding oceanic closure and continental collision processes driven by the Shangdan Ocean subduction-exhumation, which was a segment of the Proto-Tethys Ocean during the Early Paleozoic. Despite significant research, the Early Paleozoic tectonic background and subduction-related orogenic processes, particularly in the eastern NQLOB, remain subjects of debate. This study presents significant petrographic, geochemical, and geochronologic insights into the metavolcanic rocks of the Chenjiahe Group in the eastern NQLOB. Petrographic analysis reveals that these metavolcanic rocks originated in a low-grade metamorphic setting. Zircon laser ablation inductively coupled plasma mass spectrometry (LA-ICP-MS) U–Pb dating yielded ages ranging between 449.7–443.4 Ma, indicating Late Ordovician formation. Geochemical signatures of felsic and intermediate rocks exhibit calc-alkaline to high-K calc-alkaline similarities, characterized by high light rare earth elements (LREEs), low heavy rare earth elements (HREEs), and moderate Eu anomalies, consistent with a continental arc setting. In contrast, basaltic rocks display tholeiitic features with elevated large-ion lithophile elements (LILEs), reduced high-field-strength elements (HFSEs), and weak Eu anomalies, suggesting an extensional environment. These findings imply that the metavolcanic rocks evolved in a continental arc-back-arc extension setting connected with the northward subduction and exhumation of the Huluhe back-arc oceanic basin. This process was likely triggered by the northward subduction and closure of the Shangdan Ocean, culminating in the Late Ordovician amalgamation of the Qilian Block and the southwestern North China Block. This study provides critical insight into the tectonic development of the NQLOB and the broader Proto-Tethys Ocean dynamics at the northern periphery of the Eastern Gondwana.